Alternative slovenskemu modelu pogajanj o priznanju krivde - Gorkič, Primož (Podjetje in delo, 2017)
The article outlines some of the typologies on negotiated justice mechanisms in criminal procedure. These are then used to analyse plea bargaining and agreements under Slovenian Criminal Procedure Act. Even though Slovenian criminal procedure belongs to a tradition of mixed adversarial-inquisitorial procedure, it adopted several features similar to the US-style of plea bargaining. This makes it vulnerable to the same shortcomings as were observed in the US criminal justice systems. At the same time, some European criminal justice systems, in particular in England and Germany, developed solutions that incorporate plea bargaining into the trial itself. They allow for a more active judicial participation in the bargaining process. Such solutions contribute to a more transparent and accountable bargaining process, thus reducing the uncertainties faced by the defendant and the possibilities of a wrongful conviction.
Keywords: acceptance of plea agreement; court; defendants; obdolženci; plea agreement; plea bargaining; pogajanja o priznanju krivde; predobravnavni narok; pre-trial hearing; sklep o sprejemu priznanja krivde; sodišče; sporazum o priznanju krivde